Cost of overweight, obesity, and related complications in Switzerland 2021 - Steinl, David; Holzerny, Pascale; Ruckdäschel, Stephan; Fäh, David; Pataky, Zoltan; Peterli, Ralph; Schultes, Bernd; Landolt, Susanne; Pollak, Timo (Frontiers in Public Health, 2024)
Background: The prevalence of obesity has increased significantly in recent decades with today more than 1/3 of the world’s population has overweight or obesity, rendering it one of the most significant global health concerns. This article provides a current estimate of the direct costs associated with managing overweight and obesity, including treatment of related complications, among adolescents (≥ 15 years) and adults in Switzerland. Methods: Prevalence of overweight and obesity based on the BMI reported in the 2017 Swiss Health Survey was extrapolated to 2021. Systematic literature searches were performed to identify treatment costs and epidemiological data of obesity-related complications and costs were extrapolated to 2021. Treatment costs for complications attributable to overweight and obesity were estimated by their population attributable fraction (PAF). Results: More than 3.1 million. inhabitants of Switzerland aged ≥ 15 years met the criteria for overweight or obesity in 2021. The prevalence of overweight increase over the past decades from 30.4 % in 1992 to 41.9 % in 2017 while prevalence of obesity doubled from 5.4 % to 11.3 %. Overall, the total attributable costs of overweight and obesity caused by seven assessed obesity-related complications (asthma, coronary heart disease, depression, diabetes mellitus, hypertension, osteoarthritis, and stroke) are estimated at CHF 3 657 – 5 208 million with most of the costs (97 – 98 %) caused by the assessed obesity-related complications. Only 2 – 3 % of the total costs were attributable to the combined direct management of overweight and obesity by bariatric surgery (CHF 83 million), pharmacological therapy (CHF 26 million) and dietary counseling (CHF 18 million). Conclusions: Overweight and obesity impose a significant cost impact on the Swiss healthcare system, accounting for 4.2 – 6.1 % of total healthcare expenditures in 2021. Notably, direct treatment of overweight and obesity accounts for only 0,08 – 0,18 % of the total healthcare expenditures. The analysis also revealed a significant lack of available health economic evidence, necessitating the use of assumptions and approximations in this estimation. This is noteworthy, as respective data would be available in healthcare systems but are either unpublished or inaccessible.